2019
DOI: 10.1186/s12989-019-0302-8
|View full text |Cite|
|
Sign up to set email alerts
|

Particle toxicology and health - where are we?

Abstract: Background Particles and fibres affect human health as a function of their properties such as chemical composition, size and shape but also depending on complex interactions in an organism that occur at various levels between particle uptake and target organ responses. While particulate pollution is one of the leading contributors to the global burden of disease, particles are also increasingly used for medical purposes. Over the past decades we have gained considerable experience in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
119
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(119 citation statements)
references
References 367 publications
(312 reference statements)
0
119
0
Order By: Relevance
“…Nowadays, alloy is used for its superior corrosion resistance, and different types of bearing surfaces are available 49,50 . Ti particles released from Ti bulk implant or composites was confirmed by studies, and it was inevitable to apply Ti as a biomaterial, considering its outstanding mechanical property 1,2,13,14,16,17,22 . However, little is known about the interaction existing in different materials 50 .…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Nowadays, alloy is used for its superior corrosion resistance, and different types of bearing surfaces are available 49,50 . Ti particles released from Ti bulk implant or composites was confirmed by studies, and it was inevitable to apply Ti as a biomaterial, considering its outstanding mechanical property 1,2,13,14,16,17,22 . However, little is known about the interaction existing in different materials 50 .…”
Section: Discussionmentioning
confidence: 96%
“…As a result of rapid advances of the biomaterials science, reliable implants were considered to be most widely accepted operative procedure for treating damaged skeleton and diseased organs, such as various skeletal defects, tooth deficiency, joints replacements and et al Due to the routine use of implants, wear particles or debris can be observed from surfaces in relative friction between implants and physiological environment, surfaces between different component of implant, scaffolds for tissue engineering, or materials for drug delivering [1][2][3][4] . In particle disease, peri-implant osteolysis which is caused by wear particles remains the main complication for implant failure after the surgical [5][6][7][8] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past 10 years there has been increasing research to better understand the impact of environmental stressors such as pollution emissions and urban residency on skin [30]. It is known that the major impact of emitted gases and particulate matter from industrial and automotive sources on human health are respiratory effects due to direct contact, but researchers suggest that these stressors can also affect secondary organs [31,32]. This includes reactions by skin in the form of atopic dermatitis, psoriasis, and eczema flareups [33,34] and evidence that these stressors can negatively impact skin aging and appearance [5].…”
Section: Discussionmentioning
confidence: 99%
“…Particulate matter air pollution (PM) has a well-established and consistent association with cardiovascular and respiratory morbidity and mortality (1)(2)(3). This link has proven strongest for ne combustion-derived PM (particle diameter < 2.5 µm; PM 2.5 ) (4).…”
Section: Introductionmentioning
confidence: 99%